PENGARUH ATMOSFIR TOKO, KUALITAS PELAYANAN, KELENGKAPAN BARANG DAN KEWAJARAN HARGA TERHADAP NIAT BELI KONSUMEN PADA TOKO PAINLUVA SEMINYAK BALI - Upadhana, Ida Bagus Ary; Rastini, Ni Made (E-Jurnal Manajemen, 2014)
This research aims to determine the effect of store atmosphere, service quality, completeness and fairness of the price of goods to the consumer's purchase intention in Seminyak Bali Painluva Store. Painluva store, Seminyak Bali was chosen as the location of the research with 110 people sampled respondents research. The respondents are consumers who visit and for the first time shopping at Shop Painluva. Multiple linear regression analysis is used as a data analysis technique. The analysis showed that the store atmosphere, service quality, completeness and fairness of the price of goods showed a significant effect simultaneously and partially on purchase intention, this means that the better the atmosphere stores, service quality, completeness and fairness of the price of the goods purchase intention increased. Keywords: purchase intentions, store atmosphere, service quality, completeness goods, price fairness